What we have learned for the future about COVID-19 and healthcare management of it? - Charitos, Ioannis Alexandros; Del Prete, Raffaele; Inchingolo, Francesco; Mosca, Adriana; Carretta, Domenico; Ballini, Andrea; Santacroce, Luigi (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: COVID-19 is a current global pandemic. However, comprehensive global data analyses for its healthcare management are lacking.Methods: In this study we have researched through published scientific articles and international health care  guidelines to find out actually about our knowledge for this new pandemic from SARS-CoV-2 and related COVID-19 disease that emerged from December 2019 in China in order to better manage this health emergency. Results: The pathogens represented by microorganisms (bacteria, mycetes or viruses) show their effect after days and are responsible for epidemics/pandemics as dangerous as the greater their possibility of transmission, especially by inhalation, and therefore their infectivity.Conclusions: The appearance of new pathogenic viruses for humans such as the COVID -19, which previously were found only in the animal world occurs through the spillover (is the third documented of an animal coronavirus to humans), it is thought that it could also be the same also for the origin of this virus. Furthermore, the trend of this pandemic in one of the countries most affected by Italy after China was also considered.